Performance of intercropping systems based on palmarosa (Cymbopogon martinii var motia) - RAO, E V S PRAKASA; SINGH, M; RAO, R S GANESHA (The Indian Journal of Agricultural Sciences, 2013)
Â A field experiment was conducted during 1986-87 and 1987-88 to study the performance of intercropping systems based on palmarosa [Cymbopogon martinii (Roxb.) Wats. vat motia Burk.] at Bangalore. The intercropping systems were palmarosa + cowpea [Vigna unguiculata (L.) Walp.], palmarosa + blackgram (Phaseolus mungo L.) and palmarosa + green gram (Phaseolus radiatus L.) during 1986-87, and palmarosa + blackgram-blackgram, palmarosa + sorghum grain [Sorghum bicolor (L.) Moench.)-blackgram and palmarosa + sorghum fodder-ratoon during 1987-88. The results showed that the intercropping of blackgram-blackgram or smghum fodder-ratoon gave additional yields of 660 kg/ha seed and 16.6 tonnes/ha fodder respectively compared with the sale crop of palmarosa. Land-use efficiency in these intercropping systems increased by 24 and 9% respectively.